An Unusual Case of Squamoid Eccrine Carcinoma of the Abdominal Wall with Inguinal Nodal Metastases: A Case Report and Review of the Literature - Brenna L. Hennessey (Shiraz University of Medical Sciences, 2019)
Introduction: Squamoid eccrine carcinoma is a very rare carcinoma with few reported cases in the literature. As a result, there islimited guidance on management and follow-up of these cases.Case Presentation: We describe the case of a 39 year-old male with a large painful squamoid eccrine carcinoma of the right lowerabdominal wall with inguinal nodal involvement. He underwent radical resection, superficial groin dissection, transposition of asartorius muscleflap, anda pedicled anterolateral thigh perforatorflapfor reconstruction. The postoperative coursewasuneventfulapart from a postoperative seroma which was treated with aspiration. He underwent adjuvant radiation following full recoveryfrom his procedure.Conclusions: Our case study represents a rare, large squamoid eccrine carcinoma of the abdominal wall treated with radical resection,superficial groin dissection, transposition of a sartorius muscle flap, and a pedicled anterolateral thigh perforator flap forreconstruction. Due to the limited number of reported cases, there are no guidelines for management of squamoid eccrine carcinomas.With this case report we aim to increase awareness of this rare carcinoma, and to summarize the existing literature onmanagement of squamoid eccrine carcinoma.